Hubungan Tingkat Pengetahuan dengan Perilaku Pemantauan Glukosa Darah Mandiri (PGDM) Pada Pasien DM Tipe II Di RS Bali Royal Denpasar - Yunitasari, Ni Kadek Mei; Laksmi, Ida Ayu Agung (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2025)
Background: Education on Independent Diabetes Management (EIDM) is a component of comprehensive DM management through Independent Blood Glucose Monitoring (IBGM). some patients demonstrate helplessness in managing the prevention of diabetic complications due to lack of knowledge level.Purpose: This study aimed to determine the correlation between knowledge level and the Independent Blood Glucose Monitoring (IBGM) in elderly people with type II DM at the Polyclinic of X Hospital Denpasar.Methods: This study used a cross-sectional correlative descriptive method. The sampling technique used non-probability sampling, namely purposive sampling. The sample in this study consisted of 78 respondents. The Spearman rank test was utilized for the analysis.Results: The Spearman rank test was utilized for the analysis. According to the findings of the investigation, the majority of respondents have less knowledge (51.3%) and unsuccessful in implementing IBGM (80.8%).Conclusion: Based on the findings of the analysis, the p-value was 0.000<0.05, implying that there was a correlation between knowledge level and the Independent Blood Glucose Monitoring (IBGM) in type II DM patient at the Polyclinic Interna of Bali Royal Denpasar Hospital.  Health professionals are in the forefront of efforts to improve the effectiveness of IBGM in controlling blood glucose levels, hence lowering diabetes-related mortality and morbidity rates.